A study on comfort and satisfaction among public employees: Comparison between conventional & green building - Wan Mohamed Radzi, Che Wan Jasimah; Othman, Mohamad Naim (2018)
The increasing acceptance of green building concept is clue to its overwhelming outcome towards ensuring optimum use of resources which resulted in improvement of overall impact towards the environment, occupants' well-being and health. Despite the positive outcomes, only seven governments buildings have embraced the commitment to getting green building index certification in Malaysia. In fact, few studies conducted shows the impact of green building towards the well-being of its occupants has produced inconclusive and mixed results about the level of comfort and satisfaction compared to its counterparts, conventional building. Thus, the objective of the study is to investigate the differences in respondents' perceived comfort, satisfaction and sustainable practices based on conventional and green certified building. The second objective is to understand the relationship between respondent's perceived comfort and satisfaction in both buildings. The study employed a quantitative method involving correlational and cross-sectional design. The respondents comprised of public employees who were working at a newly certified building, Menara Kerja Raya at Kuala Lumpur. The respondents also had prior experiences working in conventional buildings before moving into the Menara Kerja Raya. Self administered questionnaires were distributed to 312 respondents selected through a systematic random sampling technique. furthermore, paired sample t-test was conducted to investigate whether there arc any differences in respondents' perceived comfort, satisfaction and sustainable practices while working at conventional building versus green-certified building. The results indicated that the respondents experienced a higher level of comfort (29%), satisfaction (14%) and sustainable practices (14%) while working in the green building, i.e. Menara Kerja Raya compared to while working in the conventional building. Moreover, multiple linear regression test was performed to understand the relationship between perceived comfort and satisfaction in both buildings. The finding demonstrated that there was a positive relationship between respondents' comfort and satisfaction in both buildings. In a conventional building, the result showed that comfort has 61 % influenced by satisfaction. Whereas, in Menara Kerja Raya, comfo rt has 59% influenced by satisfaction. The findings provided some evidence concerning the factors such thermal comfort, acoustic comfort, visual comfort and indoor air quality comfort that were essential for improving the level of comfort and satisfaction among respondents working in the green building. The results indicated that to turn off lights and to put the computer on sleep-mode or turn it off were the most common practices related to sustainability behaviours among respondents at both types of buildings. These findings would assist relevant government agencies to develop appropriate measures and sustainability programs to initiate more government building to be certified with green building certification. With the increased level of com fort and satisfaction as well as sustainable practices, while working in the green building, it should be a strong justification to increase the number of green building construction and development in the future.